2020
DOI: 10.1080/23748834.2020.1766783
|View full text |Cite
|
Sign up to set email alerts
|

Social return on investment analysis of an urban greenway

Abstract: Evidence supports the multi-functional nature of urban green space, and so economic evaluations should have a broad lens in order to capture their full impact. Given the evidence for a range of health, wellbeing, social and environmental benefits of such interventions, we modelled the potential social return on investment of a new urban greenway intervention in Belfast, Northern Ireland. Areas that the greenway was purported to impact upon included: land and property values; flood alleviation; tourism; labour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…Care is also required in accepting at face value the estimates reported given methodological issues that pertain to the current state of the art with respect to SROI. With these caveats in mind noted, the values reported for ACIs using the SROI approach are comparable with those from other SROI studies in other contexts including those as diverse as a first aid intervention [ 71 ], investment in urban greenways [ 72 ] and the provision of refuge services to those experiencing domestic violence [ 73 ] (a return on investment of £3.50-£4, £2.88-£5.81 and £4.94 respectively). Similarly, with respect to the study that adopted a cost-effectiveness approach, Coulton and colleagues (2015) reported a 64% probability of the intervention being cost-effective at a threshold of £30,000 [ 62 ].…”
Section: Discussionsupporting
confidence: 71%
“…Care is also required in accepting at face value the estimates reported given methodological issues that pertain to the current state of the art with respect to SROI. With these caveats in mind noted, the values reported for ACIs using the SROI approach are comparable with those from other SROI studies in other contexts including those as diverse as a first aid intervention [ 71 ], investment in urban greenways [ 72 ] and the provision of refuge services to those experiencing domestic violence [ 73 ] (a return on investment of £3.50-£4, £2.88-£5.81 and £4.94 respectively). Similarly, with respect to the study that adopted a cost-effectiveness approach, Coulton and colleagues (2015) reported a 64% probability of the intervention being cost-effective at a threshold of £30,000 [ 62 ].…”
Section: Discussionsupporting
confidence: 71%
“…In academic studies, the valuation of greenways has been an important topic because it not only shows the various benefits of greenways but also helps to justify greenway investment. For instance, in the study of a recently developed urban greenway in Belfast, Hunter et al managed to estimate various social returns, suggesting that the benefit-cost ratio ranged from 2.88 to 5.81 [15]. More specifically, "for every £1.00 invested in the greenway, there would be £2.00-6.00 returned", adding up its influences on land and property values, labor market employment and productivity, flood alleviation, climate change, health, tourism, and quality of place [15].…”
Section: Literature Review 21 Heterogeneity In the Capitalization Of ...mentioning
confidence: 99%
“…For instance, in the study of a recently developed urban greenway in Belfast, Hunter et al managed to estimate various social returns, suggesting that the benefit-cost ratio ranged from 2.88 to 5.81 [15]. More specifically, "for every £1.00 invested in the greenway, there would be £2.00-6.00 returned", adding up its influences on land and property values, labor market employment and productivity, flood alleviation, climate change, health, tourism, and quality of place [15]. In fact, the capitalization of green spaces into the value of nearby properties [16] is also found in greenways [4,17,18].…”
Section: Literature Review 21 Heterogeneity In the Capitalization Of ...mentioning
confidence: 99%
“…For objective 3, a SROI approach will be used to provide a fuller picture of system-wide UGBS health and co-benefits, and their distribution across various communities. This will build on our SROI of UGBS in Belfast and Edinburgh 59 , 60 and the findings from WP1 to include the values that matter for stakeholders, for example, health, wellbeing and NCD risk factors, and public health and planetary health co-benefits such as tourism, biodiversity, crime, and employment, and extend it to include ‘green issues’ to consider the ‘business case’ for UGBS providing sustainable food, housing and energy.…”
Section: Groundswell Work Packagesmentioning
confidence: 99%